أثر ممارسات إدارة الموارد البشرية على بناء العقد النفسي العلاقاتي للعمال الدائمين و المؤقتين - قورين, حسنية; بن عبو, الجيلالي (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى تحديد أثر ممارسات إدارة الموارد البشرية على بناء العقد النفسي العلاقاتي لكل من العمال الدائمين و العمال المؤقتين، أجريت هذه الدراسة باعتماد الاستبيان على عينة مكونة من 58 عامل بمؤسسة النقل الحضري و شبه الحضري لولاية سيدي بلعباس منهم 42 عامل دائم و 16عامل مؤقت ضمن جهاز المساعدة على الإدماج المهني. بعد المعالجة الإحصائية أسفرت الدراسة عن وجود تأثير إيجابي لممارسات إدارة الموارد البشرية على بناء العقد النفسي العلاقاتي لكل من العمال الدائمين و العمال المؤقتين قدره 39% و29.1 % على التوالي مع عدم تسجيل أية فروقات في بناء العقد النفسي بين المجموعتين تعزى لطبيعة عقد العمل. This study aims to determine the impact of human resources management practices on the construction of the relational psychological contract for both permanent and temporary workers. This study was carried out using questionnaire on a sample of 58 workers of the Urban and Sub-Urban Transport Corporation of Sidi Bel Abbes, including 42 permanent and 16 temporary workers within the professional Integration Assistance device. The statistical treatment confirmed that human resources management practices had a positive effect on relational psychological contract for both permanent and temporary workers of 39% and 29.1%, respectively, with no differences in the construction of the psychological contract between the two groups due to the qualitynature of the employment contract.
The impact of human resource management practices on the building of pshycological relational contract for permanent and temporary workkers
مقال
Keywords: العقد النفسي العلاقاتي ; ممارسات إدارة الموارد البشرية ; العامل الدائم ; العامل المؤقت